A Case of Bilateral Atrophy of the Inferior Vestibular Nerves. Issue 3 (March 2018) - Gallo, Kelsey; Jhaveri, Miral D.; Sharbidre, Kedar G.; Winston, Amy; LoSavio, Phillip S.
Abstract : N/A: We report a case of a 62-year-old woman who was found to have bilateral atrophy of the inferior vestibular nerves on magnetic resonance imaging (MRI) after presenting to our clinic with 6 years of intermittent vertigo and residual unsteadiness. The nerve atrophy may be associated with an episode of vestibular neuritis, a common cause of vertigo that exclusively involves the inferior vestibular nerve in less than 3% of cases. While MRI may demonstrate vestibular nerve enhancement in cases of acute vestibular neuritis, no single MRI finding has been demonstrated consistently among cases of acute or chronic vestibular neuritis. Physical therapy is likely an effective long-term treatment for this patient to achieve central compensation for symptomatic relief.